Effectiveness, Safety, and Side Effect of Depo Progestin and Depo Vigestron Contraception - Budi Santoso; Jimmy Yanuar Annas; Heriyadi Manan; Nizam Albadawi; Marina Marina; Maria Anggraeni; Leli Asih (Universitas Airlangga, 2013)
Introduction: Trends in contraceptive injections increased in the last two decades. Hormonal contraceptive injection is available in single or combination dose. However, the products are available more than 1 ml (more than recommendation of WHO). This study aims to determine the effectiveness, safety and side effects of the contraceptive injection Depo Progestin® 3 ml, Depo Vigestron® 3 ml and Depo Vigestron® 1 ml.Methods: This study used randomized controlled clinical trial and open label. The research subject were 900 people in two center, Surabaya and Palembang. The samples were divided into 3 (three) groups, group Depo Progestin® vial 3 ml, group Depo Vigestron® vial 3 ml, and group Depo Vigestron® vial 1 ml. Each of consist 300 women using the